2011
DOI: 10.1111/j.1475-097x.2011.01061.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface microdialysis sampling: a new approach described in a liver ischaemia model

Abstract: We recently have shown that samples from microdialysis (MD) probes placed on the surface of the heart reflect metabolic events in the myocardium. This new interesting observation challenges us to consider whether surface application of MD applies to other parenchymatous organs and their surfaces. In 13 anesthetized pigs, transient liver ischaemia was achieved by occlusion of arterial and venous inflow to the liver. Two probes on liver surface and two in parenchyma were perfused with a flow rate of 1 μl per min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…The placement of an MD probe into the parenchyma of an organ implies a certain degree of invasiveness and ensuing potential adverse effects [3]. It has recently been demonstrated that markers of ischemia as determined by MD probes placed on the surface of the myocardium and the liver are in concordance with levels within the myocardium [14] and liver parenchyma [15], respectively. These results suggest that the placement of MD probes on the surface of the pancreas could likewise provide online information on ongoing pathophysiological processes within the organ.…”
Section: Discussionmentioning
confidence: 90%
“…The placement of an MD probe into the parenchyma of an organ implies a certain degree of invasiveness and ensuing potential adverse effects [3]. It has recently been demonstrated that markers of ischemia as determined by MD probes placed on the surface of the myocardium and the liver are in concordance with levels within the myocardium [14] and liver parenchyma [15], respectively. These results suggest that the placement of MD probes on the surface of the pancreas could likewise provide online information on ongoing pathophysiological processes within the organ.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, we analyzed the selected S-mD lactate and glucose concentrations because these metabolites have shown reproducible changes related to ischemia in our previous studies. [16][17][18][19][20] When considering the lactate changes, levels reaching a plateau could depend on the relation between aerobic and anaerobic metabolism, which in turn is related to the arterial blood supply. Partially preserved microcirculation at the gastric corpus (catheter position B) Table 3 e Intracatheter comparisons of absolute values of mD lactate and mD glucose between baseline and each hour during ischemia at four catheter locations (sites A-D).…”
Section: Discussionmentioning
confidence: 99%
“…The surface microdialysis (S-mD) catheter measures concentrations of metabolites at the surface of the specific organ, is less invasive, and renders outcome in excellent agreement with intraparenchymal catheters in the heart and liver. [16][17][18] Furthermore, the S-mD method provides outcome in concordance with histopathologically graded ischemia of the small bowel. 19 S-mD allows for online detection and monitoring of organ ischemia within minutes after its onset.…”
Section: Introductionmentioning
confidence: 95%
“…; Abrahamsson et al. , ). However, not placing the catheter in the parenchyma may blunt and/or delay changes in the L/P‐ratio and therefore introduce an error.…”
Section: Discussionmentioning
confidence: 97%
“…We chose to place the microdialysis catheters, which monitored the kidney and the gut, on the surface and the lumen of the organs. These placements have been shown to mirror the L/P-ratio changes within liver, heart and gut mucosa without injuring the organs (Sollig ard et al 2004;Abrahamsson et al 2011Abrahamsson et al , 2012. However, not placing the catheter in the parenchyma may blunt and/or delay changes in the L/P-ratio and therefore introduce an error.…”
Section: Discussionmentioning
confidence: 99%